2011
DOI: 10.1105/tpc.111.086918
|View full text |Cite
|
Sign up to set email alerts
|

Multivesicular Bodies Mature from the Trans-Golgi Network/Early Endosome in Arabidopsis  

Abstract: The plant trans-Golgi network/early endosome (TGN/EE) is a major hub for secretory and endocytic trafficking with complex molecular mechanisms controlling sorting and transport of cargo. Vacuolar transport from the TGN/EE to multivesicular bodies/late endosomes (MVBs/LEs) is assumed to occur via clathrin-coated vesicles, although direct proof for their participation is missing. Here, we present evidence that post-TGN transport toward lytic vacuoles occurs independently of clathrin and that MVBs/LEs are derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
245
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(261 citation statements)
references
References 96 publications
16
245
0
Order By: Relevance
“…Alternatively, canonical RAB5 may regulate sorting for PSVs on the TGN, which is similar to reports in rice (Oryza sativa) endosperm (Ren et al, 2014;Wen et al, 2015). A subpopulation of canonical RAB5 has been localized to the TGN, which is likely responsible for maturation from the TGN to the multivesicular endosomes (Stierhof and El Kasmi, 2010;Scheuring et al, 2011;Singh et al, 2014). EREX might coordinate cargo sorting and RAB5 activity during this event, which is consistent with the findings that the mutations in AP-4 and sorting nexins that are involved in vacuolar protein transport at the TGN and RAB5-positive endosomes, respectively, exert similar effects on transport of 12S globulin and 2S albumin to the erex erel1 mutation (Pourcher et al, 2010;Fuji et al, 2016).…”
Section: How Does Erex Mediate Vacuolar Trafficking With Rab5?supporting
confidence: 48%
See 1 more Smart Citation
“…Alternatively, canonical RAB5 may regulate sorting for PSVs on the TGN, which is similar to reports in rice (Oryza sativa) endosperm (Ren et al, 2014;Wen et al, 2015). A subpopulation of canonical RAB5 has been localized to the TGN, which is likely responsible for maturation from the TGN to the multivesicular endosomes (Stierhof and El Kasmi, 2010;Scheuring et al, 2011;Singh et al, 2014). EREX might coordinate cargo sorting and RAB5 activity during this event, which is consistent with the findings that the mutations in AP-4 and sorting nexins that are involved in vacuolar protein transport at the TGN and RAB5-positive endosomes, respectively, exert similar effects on transport of 12S globulin and 2S albumin to the erex erel1 mutation (Pourcher et al, 2010;Fuji et al, 2016).…”
Section: How Does Erex Mediate Vacuolar Trafficking With Rab5?supporting
confidence: 48%
“…ARA7 and RHA1, in contrast, redundantly regulate endocytic and vacuolar trafficking pathways (Sohn et al, 2003;Kotzer et al, 2004;Dhonukshe et al, 2006;Ebine et al, 2011Ebine et al, , 2014Beck et al, 2012). The unique organization of endosomal trafficking in plants is also demonstrated by the observation that the trans-Golgi network (TGN) acts as an early endosome in plants (Dettmer et al, 2006;Lam et al, 2007;Viotti et al, 2010), from which multivesicular endosomes are proposed to be directly generated by maturation (Niemes et al, 2010;Scheuring et al, 2011). The RAB11 group (also known as RABA in Arabidopsis), which is localized to TGNrelated secretory compartments and is involved in cell plate formation and tip growth (Preuss et al, 2004;Chow et al, 2008;Szumlanski and Nielsen, 2009;Kang et al, 2011;Feraru et al, 2012;Asaoka et al, 2013;Berson et al, 2014;Kirchhelle et al, 2016), is also implicated in endosomal/vacuolar trafficking (Bottanelli et al, 2011;Choi et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Despite the same concentration of sugar in the medium, TEM analysis of the mesophyll chloroplasts of the adventitious R. tianschanicus 9 R. patientia shoots revealed strong differences in the ultrastructure of the chloroplasts in the leaves of the adventitious shoots that had been regenerated in vitro, before rooting. Similar to Scheuring et al (2011), we observed in this case vesicles and cytoplasmic materials in the vacuoles as well as multivesicular bodies.…”
Section: Discussionsupporting
confidence: 68%
“…GFP-ARA7 resides on MVBs (Reichardt et al, 2007), which serve as PVCs and are usually referred to as late endosomes (Richter et al, 2009). A very recent study has demonstrated that MVBs mature from the TGN, which serves as a landing station for proteins arriving from the PM (Scheuring et al, 2011). Therefore, if endocytosed PM proteins do not enter the recycling pathway, they become ubiquitinated and are targeted for degradation.…”
Section: Discussionmentioning
confidence: 99%